مقالات الفرق الإسلامية في مفهوم الإيمان عند ابن حزم من خلال كتابه "الفَصْل في الملل والنحل": عرض ونقد: The concept of faith according to Islamic sects in Ibn Hazm's book: Al-Fasl fi al-Milal wa al-Nihal: A View and Critique - kais, Saidi (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث يرى بعض الباحثين أن ابن حزم الأندلسي قد تحرى الدقة في ضبط مقالات الفرق في كتابه: الفَصْلُ في الملل والنحل، ويرى البعض الآخر عكس ذلك، أي أنه قد وقع منه أخطاء وأوهام في عزو بعض المقالات إلى أصحابها، غير أنهم يعتذرون له ويرون أن هذا الخلل كان بسبب شحة المصادر والمراجع في بلاده الأندلس زمن تأليفه لكتابه، وذلك نظرا لبعد بلاد الأندلس عن المشرق الإسلامي وتأخر وصول الكثير من كتب العلماء المشارقة إليها إلى ما بعد وفاة ابن حزم. ويتناول هذا البحث دراسة مسألة تعريف الإيمان عند الفرق الإسلامية في كتاب: الفَصْل في الملل والنحل لابن حزم، باعتباره نموذجا نحاول من خلاله معرفة أي الرأيين كان أقرب إلى الحق، ولتحقيق هذا الهدف اعتمدت هذه الدراسة المنهج الاستقرائي التحليلي القائم على تتبع وتحليل ما عزاه ابن حزم من مقالات للفرق في باب تعريف الإيمان، والمنهج النقدي المقارن للنظر والتحقق في مدى دقة ابن حزم في عزوه لتلك المقالات إلى أصحابها، وقد توصلت الدراسة إلى ترجيح القول الثاني وهو أن ابن حزم قد وقع منه عدة أخطاء وأوهام في نسبة مقالات الفرق في تعريف الايمان إلى أصحابها. ABSTRACT Some researchers hold that Ibn Ḥazm al-Andalusī was precise in documenting the views of the sects in his book, Al-Faṣl fī al-Milal wa-al-Niḥal, while others hold the opposite view, in other words, that he made errors in attributing some views to their adherents. However, they excuse him, believing that this flaw was due to the scarcity of sources and references in his country, Andalusia, at the time he authored his book, because of Andalusia's remoteness from the Islamic East and the delayed arrival of many books by Eastern scholars until after Ibn Ḥazm's death. This research addresses the issue of the definition of faith (Īmān) among Islamic sects in his book, Al-Faṣl, considering it a model through which we attempt to determine which of the two opinions is closer to the truth. To achieve this objective, this study adopted the inductive-analytical method to trace and analyse the views that Ibn Ḥazm attributed to the sects in the chapter on the definition of faith, and the comparative-critical method to examine and verify the accuracy of his attribution of those views to their adherents. The study concluded by favouring the second opinion, which is that Ibn Ḥazm made several errors in attributing the views of the sects on the definition of faith to their adherents.